1980
DOI: 10.1152/ajprenal.1980.239.3.f206
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic stimulation and electrolyte excretion: a micropuncture study

Abstract: The anterior part of the lateral hypothalamus was stimulated by injection of carbachol through a stereotaxically implanted cannula in the rat. Re-collection micropuncture experiments showed that this procedure, which leads to diuresis and natriuresis with only transient changes in glomerular filtration rate and renal plasma flow, reduced the TF/P inulin ratio along proximal and distal tubules without significant alteration of single nephron glomerular filtration rate in most experimental groups. Fractional pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In a recollection micropuncture experiment along proximal and distal renal tubules, it was found that carbachol stimulation of the lateral hypothalamic area (LHA) led to diuresis and natriuresis with only transient changes in GFR and renal plasma flow. These effects are only partially due to the release of neurohypophysial hormones, since the administration of OT and AVP promoted a further effect of LHA stimulation (479). Silva-Netto et al (478) have also shown the natriuretic effect of carbachol stimulation of the LHA in rats with intact or denervated kidneys.…”
Section: Role Of ␣-Adrenergic and Cholinergic Receptors In Controlmentioning
confidence: 98%
See 1 more Smart Citation
“…In a recollection micropuncture experiment along proximal and distal renal tubules, it was found that carbachol stimulation of the lateral hypothalamic area (LHA) led to diuresis and natriuresis with only transient changes in GFR and renal plasma flow. These effects are only partially due to the release of neurohypophysial hormones, since the administration of OT and AVP promoted a further effect of LHA stimulation (479). Silva-Netto et al (478) have also shown the natriuretic effect of carbachol stimulation of the LHA in rats with intact or denervated kidneys.…”
Section: Role Of ␣-Adrenergic and Cholinergic Receptors In Controlmentioning
confidence: 98%
“…Several other laboratories have also made important contributions to understanding of the role played by the CNS in the control of body fluid homeostasis (for review, see Refs. 9, 65, 121, 135,153,170,172,255,257,478,479).…”
Section: A Control Of Hydromineral Balance By a Brain Neural Circuitmentioning
confidence: 99%
“…Central administration of carbachol induces diuretic, natriuretic, and kaliuretic responses in adults (43)(44)(45). An increase of blood pressure may affect renal excretion (5).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, studies have shown that electrolytic lesion of the hypothalamic regions in conscious rats reduces salt intake and the pressor response to cholinergic and noradrenergic microinjection into the median preoptic nucleus (Covian et al, 1975). Prior findings have also revealed that central α- and β-adrenergic receptors response are involved in CNS hydrosaline homeostasis (Gontijo and Kopp, 1994; Covian et al, 1975; Silva-Netto et al, 1983, 1980; Franci et al, 1980; Gontijo et al, 1991; Gontijo et al, 1990).…”
Section: Introductionmentioning
confidence: 98%